Profitability, Leverage, and Size as Drivers of Firm Value: A Study of Indonesian Manufacturing Companies - Yahya, Hilmi Agni Rajabbi; Yulianto, Agung (International Journal of Economics, Business and Innovation Research, 2026)
This analyze aims to evaluate impact of profit, debt ratio, and firm size on the value of a manufacturing company the in processed food subsector itemized at the Indonesia Stock Exchange span period from 2022 to 2024. This research plan uses a causal associative study approach. In this study, trial was taken untilizing the purposive approach sampling. The analyzed data in this study includes 101 companies, of which 55 companies were selected as samples for a three-year observation period (2022-2024). The technique used to analyze the data is multiple linear regression. Centered the on test outcome, it able to be concluded data that from this study match necessary classical presumptions, including normality, and are available no are issues of multicollinearity, heteroscedasticity, and autocorrelation. The outcome of the fractional hypothesis assessment that donate profitability impacts the of firm value. From the outcome findings, can it deduced be that profitability performs crucial an part in influencing the firm value, indicating that capability the company's to create surplus a key is factor in increasing firm value. Meanwhile, leverage and firm size had no impact, indicating that debt levels and firm size are not determining factors in determining firm value.